The incidence and economic burden of injuries in Jiangxi, China. (September 2016) - Fang, X.; Zeng, G.; Linnan, H.W.; Jing, R.; Zhu, X.; Corso, P.; Liu, P.; Linnan, M.
Abstract: Objectives: This study estimated the incidence, direct medical and non-medical costs, and productivity losses due to morbidity and mortality across multiple strata for injuries that occurred in Jiangxi, China. Study design: Cross-sectional study. Methods: Data came from the Jiangxi injury survey, a provincially-representative, population-based sample of 100, 010 households. The major economic costs of injuries were divided into direct costs and indirect costs. Direct costs encompass medical costs and direct non-medical costs. Indirect costs refer to the productivity losses due to injury-related morbidity and mortality. Results: In 2005, about one of 18 residents in Jiangxi, China, experienced an injury. Overall, fall, animal bite, and road traffic crash (RTC) injuries accounted for more than 66% of all injuries, while fall, RTC, drowning, and self-harm injuries accounted for 80% of fatal injuries. Average cost per case for a fatal injury was 163, 389 RMB (20, 171) for lost productivity and 2800 RMB (346) in direct medical & non-medical costs. A non-fatal injury resulting in hospitalisation or permanent disability on average caused 5221 RMB (643) in direct costs and 18, 437 RMB (2276) in lost productivity and, an additional loss of three school days. A non-hospitalised non-fatal injury on average caused 303 (37) RMB in direct costs and 491 RMB (61) in lost productivity and, an additional loss of 0.5 school days. Conclusions: The unequivocal evidence of the substantial health and financial burden of injuries indicates to Chinese policy makers that more research and efforts are needed to find efficacious and cost-effective interventions targeting injury. Highlights: We estimate the incidence and economic burden of injuries in Jiangxi, China. Data came from one of the largest community based injury surveys ever conducted in a developing country. About one of 18 residents in Jiangxi experienced an injury in 2005. Fall, animal bite, and road traffic crash injuries accounted for more than 66% of all injuries. On average, each injury generated 7124 RMB (880 US dollars) in direct and indirect costs.